(untitled) (AYUSHDHARA, 2018)
In the world of competition, every child stood in the race for first position. This may exposing the young brains for educational and competitive stress, eventually result in an inability to concentrate and affect memory and the level of cognition. To overcome the situations nootropics are use as brain boosters or memory enhancer. In Ayurveda many Yogas are recommended to use as Medhya (brain booster) in children, Swarnayog is one of them. This study was design to evaluate the nootropic effect of Swarnayog in school children. Normal children without having any physical or mental illness of age group 7-9 yrs was selected. Further they were evaluated for IQ and school performance report. The IQ was not less than 70 and the school performance report was not less than 40% was considered for the study. Total of 60 children were enrolled and randomly divided in two groups A & B. A was treatment and B was control group. The group A was received Swarnayog in the dose of 5 drops per day in morning hours and the group B was received Honey as placebo in the dose of 5 drops per day in morning hours for the period of 30 days. The day 31 children are assessed for general health condition and further on the day 60 children were assessed for academic performance and IQ level. The effect of Swarnayog on group A for academic performance was statistically significant compared with group B, the p value < 0.05= the level of significance. The effect of Swarnayog on group A for IQ was statistically significant compared with group B, the p value < 0.05= the level of significance. The study was found that group A showed significant effect compared to group B, it showed the positive changes in academic performance & IQ score. Thus the Swarnayog was a good nootropic drug, further study will require for their pharmacodynamic and pharmacokinetic actions.